(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
Responses of two bacteria isolated from the contamination of laboratory stock culture of phenol degrading bacteria against the stresses induced by phenol, temperature, pH and antibiotics were studied. The isolated bacteria were found to belong to the genus Streptobacillus and Corynebacterium. Growth of these two isolates on phenol resulted in changes in cell shape from rod to cocci as well as the reduction of cell size. Cell shape and size remained unchanged in nutrient broth. There was a decrease in optical density and increase in cell surface hydrophobicity when grown on phenol. Bacterial adherence to hydrocarbons assays showed cells grown on higher concentrations of phenol to be more hydrophobic than those grown on phenol with lower concentrations. Changes in growth of these two isolates were also evident for changing pH and temperature from their optimal as their response to these stresses. Antibiotic Susceptibility Test showed that both isolates were resistant to Amoxicillin and susceptible to tetracycline and phenoxymethylpenicilline. Key words: Streptobacillus; Corynebacterium; Stress; Growth; Hydrophobicity DOI: 10.3329/jbas.v34i2.6857 Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 133-141, 2010